2021
DOI: 10.1186/s13012-021-01086-3
|View full text |Cite
|
Sign up to set email alerts
|

A cluster randomized controlled trial comparing Virtual Learning Collaborative and Technical Assistance strategies to implement an early palliative care program for patients with advanced cancer and their caregivers: a study protocol

Abstract: Background Virtual Learning Collaboratives (VLC), learning communities focused on a common purpose, are used frequently in healthcare settings to implement best practices. Yet, there is limited research testing the effectiveness of this approach compared to other implementation strategies. This study evaluates the effectiveness of a VLC compared to Technical Assistance (TA) among community oncology practices implementing ENABLE (Educate, Nurture, Advise, Before Life Ends), an evidence-based, ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 74 publications
(103 reference statements)
0
8
0
Order By: Relevance
“…Multiple reviews in health care and the field of dissemination and implementation science have shown that passive implementation strategies (e.g., distributing published or printed recommendations) and even traditional training strategies (e.g., workshops, lectures) are not effective in changing provider behavior and/or implementing evidence-based practices. [37][38][39] Moreover, using a single implementation strategy to foster practice change is less effective, in general, than multi-component strategies. [40][41][42] As is highlighted in Table 1, a learning collaborative is a multi-component strategy.…”
Section: Evidence-base For Learning Collaborativesmentioning
confidence: 99%
“…Multiple reviews in health care and the field of dissemination and implementation science have shown that passive implementation strategies (e.g., distributing published or printed recommendations) and even traditional training strategies (e.g., workshops, lectures) are not effective in changing provider behavior and/or implementing evidence-based practices. [37][38][39] Moreover, using a single implementation strategy to foster practice change is less effective, in general, than multi-component strategies. [40][41][42] As is highlighted in Table 1, a learning collaborative is a multi-component strategy.…”
Section: Evidence-base For Learning Collaborativesmentioning
confidence: 99%
“…The main guiding basis of intensive care is evidence-based medicine, and nursing staff can achieve good care by communicating with patients, can provide patients with more valuable care, can achieve targeted care, and can improve patient outcomes by integrating various elements, and after care, the quality of patient survival is significantly improved and the risk of patient infection is significantly reduced [ 24 ]. Oncology via patients with high psychological stress and loss of confidence in life and the application of the PICC catheter approach to intravenous infusion, where foreign bodies are implanted in the patient's body, can lead to physical discomfort symptoms, which disturbs the patient's life and aggravates anxiety [ 25 ]. By providing health education and psychological intervention to the patients, the nursing staff helped to relieve the patients' anxiety and depression and speed up the time of disappearing symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 depicts how publications were assessed and selected for inclusion in the review. 17 had an "A vs. A+" structure (9,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26), 26 had an "A vs. B" structure (8, 27-51) and 2 had unique structures that did not fall into the two defined categories (52,53).…”
Section: Phase 1: Narrative Reviewmentioning
confidence: 99%